Seasonal to interannual variability of the tide in the Amazon estuary. (15th February 2023) - Fassoni-Andrade, Alice César; Durand, Fabien; Azevedo, Alberto; Bertin, Xavier; Santos, Leandro Guedes; Khan, Jamal Uddin; Testut, Laurent; Moreira, Daniel Medeiros
Abstract: The Amazon River exports the largest volume of fresh water to the ocean worldwide. Although previous studies have revealed the spatiotemporal tidal variability of the estuary, its hydrodynamics is still poorly understood. Here we evaluate the seasonal and interannual variability of the tide from Óbidos (800 km upstream) to the Atlantic Ocean and show how it is affected by the hydrological regime of the Amazon River. A high-resolution 2D hydrodynamic model was applied in this region at the scale of the whole estuary. The tide model is validated using data from 14 water level stations and shows an average complex error of 16 cm in the low flow season and 23 cm in the high flow season. The semi-diurnal tide is highly variable at seasonal timescales, and the seasonality of the discharge affects the tidal amplitude, the geographic extent of tidal influence, the tidal wave celerity, and the tidal flow reversal. Notably, the tidal influence on water level remains detectable up to Óbidos during the low flow season while during the high flow season it extends from the ocean to only 300 km downstream of Óbidos. On the other hand, the upstream limit of the domain where the tide induces a periodic flow reversal is different from the limit of tidal influence on the water level. The upstream limit of this flow reversal is shifted by 170 km (from 500 km to 670 km downstream of Óbidos) along the year due to the seasonality of the discharge. At interannual scale, anomalous hydrological discharges affect the tidal amplitude by up to 30% in the central reach of the estuary. Our findings open unprecedented opportunities to understand biogeochemical and geomorphological processes, help navigation, and assess flooding hazards. Highlights: Advances in modeling the impact of Amazon River variability on tidal modulation. Tidal amplitude and phase are well represented with a complex error of order 20 cm. River discharge controls tidal range, tidal celerity, and flow reversal. Extreme discharges induce changes of 10–25% of the tidal range in the central estuary.